Detecting Major Problems in Learning English Through Blog-based Class - Budianto Hamuddin; Kurniawan Kurniawan; Syaifullah Syaifullah; Herdi Herdi (Journal of Education and Learning (EduLearn), 2018)
Students’ blog in PBIG Unilak have been used to promote English skills during these two years. This mixed method study aimed to identify and describes the major problems faced by the students during the implementation of blogging based class. This study based its data from 168 students who attended 5 different classes based-blog. Employing a total sampling technique, the students were invited to fill up online questionnaire and interview. However, only 161 feedbacks can be processed. The analysis in this study reveals there are three major problems in blog-based class, which significantly contributed to an unproductive learning process atmosphere at PBIG Unilak namely: Lack of confidence in posting article and comments in the blog; Lack of IT skills and Cyberbullying.